Physical and psychosocial impacts of pregnancy on adolescents and their coping strategies: A descriptive study in Kuala Lumpur, Malaysia - Vin S.X.; Muhammad N.A.; Sun T.P.; Meng K.T.T.; Tohid H.; Omar K. (Malaysian Public Health Physicians Association, 2024)
Indexed by Scopus